Indoor environmental factors associated with wheezing illness and asthma in South Korean children: phase III of the International Study of Asthma and Allergies in Childhood. (November 2014) - Chae, Yoomi; Hahm, Myung-Il; Ahn, Kangmo; Kim, Jihyun; Kim, Woo Kyung; Lee, So-Yeon; Park, Yong Mean; Han, Man Yong; Lee, Kee-Jae; Kwon, Ho-Jang
Abstract Background: The relationship between exposure to indoor environmental pollutants and incidence of asthma and wheezing illness in children is unclear. This study aimed to clarify this relationship by identifying the risk factors associated with these conditions in South Korean children aged 6–7 years. Methods: The parents or guardians of 3810 children aged 6–7 years who had participated in the International Study of Asthma and Allergies in Childhood and met the study criteria completed validated questionnaires regarding their children's asthma and wheezing illness, risk factors and exposure to indoor pollutants. The data were subjected to chi-square and multivariate logistic regression analysis to identify the factors significantly associated with asthma and wheezing illness. Results: Parental history of allergic disease (odds ratio [OR]: 1.729; 95% confidence interval [CI]: 1.447–2.066), living on the basement or semi-basement floor (OR: 1.891; 95% CI: 1.194–2.996) and living in housing that had been remodeled within the last 12 months (OR: 1.376; 95% CI: 1.101–1.720) were found to be significantly associated with wheezing illness. Parental history of allergic disease (OR: 2.189; 95% CI: 1.483–3.231), male sex (OR: 1.971; 95% CI: 1.369–2.838) and positive skin prick test (SPT) result (OR: 1.583; 95% CI: 1.804–3.698) were found to be significantly associated with current asthma. Conclusions: Although the risk factors for current asthma appear to be more related to the non-modifiable risk factors like sex, parental history of allergic diseases, SPT, the two groups are associated with exposure to modifiable indoor environmental factors.